2020
DOI: 10.1016/j.psj.2019.11.041
|View full text |Cite
|
Sign up to set email alerts
|

A review on yolk sac utilization in poultry

Abstract: During incubation, embryonic growth and development are dependent on nutrients deposited in the egg. The content of the yolk can be transferred to the embryo in 2 ways: directly into the intestine via the yolk stalk or through the highly vascularized yolk sac membrane. It has been suggested that, as a result of genetic selection and improved management, the increase in posthatch growth rate and concurrently the increase in metabolic rate of broiler chickens during the last 50 yr has also increased embryonic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 93 publications
1
69
0
4
Order By: Relevance
“…Breeder age and egg size affect egg composition (see review by van der Wagt et al., 2020 ). Larger eggs from hens of the same age flock have a greater percentage of albumen than yolk compared with smaller eggs ( Vieira and Moran, 1998 ).…”
Section: Formation Of the Yolk And Yolk Sacmentioning
confidence: 99%
See 1 more Smart Citation
“…Breeder age and egg size affect egg composition (see review by van der Wagt et al., 2020 ). Larger eggs from hens of the same age flock have a greater percentage of albumen than yolk compared with smaller eggs ( Vieira and Moran, 1998 ).…”
Section: Formation Of the Yolk And Yolk Sacmentioning
confidence: 99%
“…In addition to this natural degradation of the YS tissue, any disruption in absorption of the YS content may lead to deficiency of necessary nutrients and maternal antibodies that can result in early chick mortality and poor chick quality. For a comprehensive analysis of the effects of broiler breeder, egg size, egg storage, and incubation temperature on yolk utilization, see the recent review by van der Wagt et al. (2020) .…”
Section: Introductionmentioning
confidence: 99%
“…The results were in line with our previous studies, which showed that an increase in ADG and a decrease in ADFI and F/G as dietary increased ME levels in the diet of starter [ 21 ] and growing [ 13 , 22 ] Pekin ducks. In addition, as the dietary ME level decreased from 12.52 to 11.54 MJ/kg, we observed that the BW and ADG were significantly decreased starting at the second week ( Figure 1 ), which might be due to the yolk sac in the body of the duckling that provided the nutrients for the first week [ 23 , 24 ]. However, Met deficiency led to poor growth performance starting in the first week ( Figure 2 ), which suggested that the growth response to dietary Met concentration for ducklings of one week of age might be greater than that to dietary ME concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Development and growth of poultry embryos are dependent upon the nutrient deposits in the eggs [19]. The yolk sac provides the chicken embryo with essential minerals nutrients for embryonic growth [20,21].…”
Section: Discussionmentioning
confidence: 99%